OP038 Hobit- and Blimp1-driven tissue resident memory T cells critically control chronic intestinal inflammation. (16th January 2018) - Zundler, S; Becker, E; Spocinska, M; Parga-Vidal, L; Stark, R; Atreya, R; Rath, T; Leppkes, M; Neufert, C; Atreya, I; van Gisbergen, K; Neurath, M F
Abstract: Background: Tissue resident memory T (TRM) cells expressing CD69 and often co-expressing CD103 reside in peripheral tissues without recirculating. In contrast to the "traditional" central and effector memory T-cell subsets, they form a first-line of adaptive immune defense in mucosal tissues. An important role in anti-viral immunity and cancer is well established, but their contribution to inflammatory bowel diseases is unknown. Recently, the transcription factors Hobit and Blimp were identified as crucial regulators of mouse TRM cell development. Methods: TRM cell markers in human gut samples from IBD patients and controls were analysed by qPCR, immunohistochemistry and flow cytometry. Hobit × Blimp1 double knockout, Hobit knockout and wildtype mice were used in experimental colitis models. Results: Significantly more TRM cells were identified in active Crohn's disease and ulcerative colitis compared with gut tissue from control patients (Figure 1A). Similarly, expression of CD69 as main residency marker was elevated in IBD vs. controls and in patients with high vs. low disease activity. The expression of several pro-inflammatory cytokines was significantly correlated with the abundance of CD69 in the inflamed mucosa. Moreover, flare-free survival in both Crohn's disease and ulcerative colitis patients with high CD69 expression was significantly lower than in patients with low CD69 expression (Figure 1B). Acute DSS colitis in Hobit × Blimp1 double knockout (DKO) mice was markedly less severe compared with wildtype mice as demonstrated by analysis of weight, endoscopy, histology and in vivo imaging of reactive oxygen species (Figure 1C). Chronic DSS colitis and T-cell transfer colitis experiments yielded compatible results. The expression of TRM cell markers and pro-inflammatory cytokines in Hobit × Blimp1 DKO mice were reduced. Corroborating these data, local depletion of colon TRM cells using an alternative method protected from subsequent TNBS-induced colitis. Conclusions: Our data are consistent with a crucial role of TRM cells in the pathogenesis of IBD. Thus, TRM cells appear to be important for the orchestration of inflammatory networks not only in the context of pathogen defense but also in the case of dysregulated immune cell activation in response to luminal antigens. TRM cells might thus represent an interesting future target for IBD therapy.